Ritmester Axel Sehested og Fru Øllegaard Thott i Brøndbyvester 1664-1692 - Jørgensen, J.P. (Historisk Årbog for Roskilde Amt, 2026)
Ritmester Axel Sehested og Fru Øllegaard Thott i Brøndbyvester 1664-1692